Peran Perpustakaan dalam Pengembangan Budaya Rejang di Perpustakaan SMAN 1 Rejang Lebong - Murdani, Hati; Rizkyantha, Okky; Saputra, Egun Dalan; Atriani, Febi (Jurnal Tadwin, 2022)
of libraries in developing and preserving culture. The role of the library of SMAN 1 Rejang Lebong in the Rejang cultural heritage container with the Rejang Corner which contains various information on Rejang culture. Where the library of SMAN 1 Rejang Lebong is located in the middle of the Rejang tribal environment. This research is a qualitative descriptive study. The results showed that the library of SMAN 1 Rejang Lebong has carried out one of the cultural functions. The Rejang Corner Service is located on the 2nd floor of the SMAN 1 Rejang Lebong Library. The activities from the rejang corner are (1) the display of rejang traditional goods, (2) the rejang corner is included in the reference service, (3) the obstacles include lack of funds, lack of support from related parties, and difficulty in getting goods. related to rejang customs.